2017
DOI: 10.3390/ijms18040673
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Melatonin on Liver Injuries and Diseases

Abstract: Liver injuries and diseases are serious health problems worldwide. Various factors, such as chemical pollutants, drugs, and alcohol, could induce liver injuries. Liver diseases involve a wide range of liver pathologies, including hepatic steatosis, fatty liver, hepatitis, fibrosis, cirrhosis, and hepatocarcinoma. Despite all the studies performed up to now, therapy choices for liver injuries and diseases are very few. Therefore, the search for a new treatment that could safely and effectively block or reverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
67
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 168 publications
(196 reference statements)
3
67
0
3
Order By: Relevance
“…Melatonin has protective effects against oxidative stress followed by inflammation caused by reactive oxygen species (ROS) or reactive nitrogen species . Therefore, melatonin administration shows therapeutic effects in various disorders including liver diseases . Melatonin has potentials for novel treatments of liver diseases by decreasing oxidative stress or restoring circadian rhythms and functions.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin has protective effects against oxidative stress followed by inflammation caused by reactive oxygen species (ROS) or reactive nitrogen species . Therefore, melatonin administration shows therapeutic effects in various disorders including liver diseases . Melatonin has potentials for novel treatments of liver diseases by decreasing oxidative stress or restoring circadian rhythms and functions.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin has been shown to be associated with the severity of liver insufficiency in patients with liver cirrhosis (7). Several studies have shown that melatonin has protective effects in several diseases, including cholestatic liver injury, alcohol-induced liver injury, nonalcoholic fatty liver disease, liver fibrosis and cirrhosis, and hepatocarcinoma (8)(9)(10)(11). We have shown that prolonged exposure to dark reduces biliary hyperplasia and liver fibrosis in bile-ductligated (BDL) rats by enhanced melatonin synthesis and down-regulation of selected clock genes (8).…”
mentioning
confidence: 99%
“…It protects various tissues from persistently produced free radicals and significant anti‐inflammatory and immunomodulatory activity, as well as oncostatic properties . Preliminary tests in human subjects have shown the beneficial effect of exogenous MLT in preventing ulcerative colitis, colon cancer, nonalcoholic fatty liver disease, and complications associated with partial liver resection …”
Section: Introductionmentioning
confidence: 99%
“…Chronic liver diseases cause progressive destruction of the liver parenchyma and accumulation of the extracellular matrix (ECM), increased collagen synthesis, and inability to promote ECM degradation, resulting in fibrosis and subsequent liver cirrhosis, which is the 10th leading cause of death in the Western world. 1,2 Liver fibrogenesis is triggered by increased reactive oxygen species (ROS), 3 leading to an inflammatory process by activating profibrogenic mediators, such as transforming growth factor beta (TGF-β). TGF-β induces the activation of hepatic stellate cells (HSC) to differentiate into myofibroblasts, thus increasing the expression of cytokines and proteins involved in matrix remodeling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation